Effectiveness of Interactive Learning Media Based on Virtual Laboratory on Scientific Literacy and Concept Mastery in Dynamic Electricity - Asnianti A. Awila; Tirtawaty Abdjul; Muhammad Yusuf; Abdul Haris Odja; Mursalin Mursalin; Supartin Supartin (Postgraduate, University of Mataram, 2025)
Scientific literacy is an individual's ability to apply scientific knowledge, identify questions, and draw conclusions based on evidence to understand and make informed decisions about the natural world and changes resulting from human activities. This study aims to analyze the effectiveness of interactive learning media based on the Virtual Laboratory in enhancing scientific literacy and improving students' conceptual understanding of the Dynamic Electricity. The study employed a quasi-experimental design, specifically the One-Group Pretest–Posttest Design, without a control group. The research subjects consisted of four ninth-grade students from two schools, namely SMPN 3 Pagimana and SMPN 5 Pagimana, totaling 80 students. The research instruments consisted of a science literacy test and a concept mastery test, each consisting of 10 essay questions and validated by experts. The results showed that the use of Virtual Laboratory media effectively improved students' science literacy, as indicated by a significant increase in scores on the posttest compared to the pretest. Statistical analysis using a paired sample t-test yielded a significance value < 0.05 in all classes, indicating a meaningful difference between students' initial and final abilities. Furthermore, the Normalized Gain (N-gain) value was in the high category (0.93–0.97). Thus, interactive learning media based on Virtual Laboratories have proven effective in improving students' science literacy and concept mastery of the Dynamic Electricity, and can serve as an alternative solution in science learning in schools with limited laboratory facilities